مناهج تعليم المرأة في الأندلس - العبدالكريم، فوزية بنت عبدالمحسن بن عبدالكريم; ابن سبل، منيرة بنت خالد بن يوسف (جامعة المنصورة - كلية التربية, 2023)
هدفت الدراسة الكشف عن مناهج تعليم المرأة في الأندلس، واستخدمت الباحثة للإجابة عن أسئلة الدراسة، المنهج التاريخي من خلال الرجوع إلى المصادر التاريخية الأصلية، والثانوية، للنظر في الأدلة، والحقائق الواردة، والمنهج الاستقرائي للحكم على الوقائع، وتعميمها، أو وصفها كحالات عينيّة وقصرها على تلك الحالات، واشتملت الدراسة على إطار عام شمل مقدمتها وموضوعها وأسئلتها وأهدافها وأهميتها ومنهجها وحدودها والدراسات السابقة، ثم محورين المحور الأول عن تعليم المرأة الأندلسية في مرحلة الكتاب، والثاني عن تعليمها في مرحلة ما بعد الكتاب، وأشارت نتائج الدراسة إلى ما يلي: تعلّمت الفتاة في مرحلة الكتّاب عدد من المناهج، هي: القرآن الكريم، والكتابة والخط، واللغة والنحو، والحساب، ودرست الفتيات في مرحلة الكتّاب، أشعارَ العرب ممّا فيه حكمة، وحث على مكارم الأخلاق، وكتابَي: الواضح في النحو، ومختصر العين في اللغة للزُّبيدي، تعلّمت المرأة بعد مرحلة الكتّاب، العلومَ الشرعية، وهي: القرآن وعلومه، والحديث وعلومه، والفقه وأصوله، وعلوم اللغة العربية (النحو، والأدب، واللغة، والعروض) وعلم الأخبار والسير، وعلم الطب. This study aimed to explore the curricula of women's education in Al-Andalus. The researcher utilized the historical methodology by referring to primary and secondary historical sources to examine the evidence and facts. The study employed an inductive approach to generalize or describe specific cases and used a framework that encompassed an introduction, topic, research questions, objectives, significance, methodology, limitations, and previous studies. The study focused on two main dimensions: the education of Andalusian women in the preliterate stage and their education in the post-literate stage. The study's findings indicated the following: during the preliterate stage, girls learned various subjects, including the Quran, writing and calligraphy, language and grammar, and arithmetic. In this stage, girls also studied Arabic poetry that contained wisdom and moral lessons, as well as textbooks such as "Al-Wadih fi al-Nahw" and "Mukhtasar al-Ayn fi al-Lughah" by Al-Zubaidi. After the preliterate stage, women pursued religious sciences, including the Quran and its sciences, hadith and its sciences, Islamic jurisprudence and its principles, Arabic language sciences (grammar, literature, linguistics, and rhetoric), as well as news and biography studies and medicine.
Keywords: المجتمع الأندلسي -- تعليم المرأة -- المناهج التعليمية